FINANCIAL CRISIS AND DEMOCRACY: FISCAL DISCPLINE AND POLITICAL PROCESSES IN EUROZONE - Гольцман, К.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The article examines the impact of current financial-economic crisis in EU on democratic processes in centre, periphery and supranational level of this integration entity. Based on the case-studies of debt crisis in Greece in 2010-2012 the argument is put forward that the fiscal discipline policy that is applied in the periphery of EU under the influence of international creditors results in the degradation of democracies in these countries. At the same time, at the supranational level of EU the trend of frequent utilization of conditionality mechanisms is evident. It is aimed at leveraging political processes in Eurozone by the international financial elite.